Stress and Its Associated Factors among Students of the College of Nursing University of Baghdad - Mohammed, qahtan; Sajit, kareem (Iraqi National Journal of Nursing Specialties, 2016)
Objectives: The current study aims at identifying the level of perceived stress among nursing college students and determining the factors associated with stress they have. Methodology: A cross-sectional descriptive study initiated for the period on November 1st, 2014 to May 1st, 2015. The study has been conducted on the undergraduate nursing college students / University of Baghdad. The sample of the study was consisted of (128) students who were selected purposively. The questionnaire of the study was adopted and modified for the present study which consisted of socio-demographic data and the scale of perceived stress among nursing students. The data have been collected through the utilization of the self administrative questionnaire as a mean of data collection. Statistical analyses were conducted by using statistical package for social science (SPSS) version 20.0. Results: The results of the study revealed that more than half of the students were male (57%) from the second academic year (60.9%) who were resident in students’ home (78.9%) and studying 2- 4 hours/day (53.1%) and sleeping 3-6 hours/day (90.6%). Undergraduate nursing students have moderate level with high percentage of 99.2%. The study also revealed the factors associated with stress among the students which are: environmental related factors include, change in the environment (85.9%), inadequate safety and security (69.5%), lack of recreational facilities (72.7%), absence of calm environment (64.8%), and inadequate of water provision (72.7%); intrapersonal related factors include, feeling of homesick (78.9%), change in sleeping pattern (78.1%), and decline in personal health (70.3%); academic related factors include lack of rest between lecture (100%), imbalance between holiday and study time (78.1%), burdens of the study and getting lower grade than anticipation (100%), inability to enjoy the study (70.3%), and stressor of practical training (77.3%); and interpersonal related factors include, fight with close one (47.7%) and conflict with roommate (51.6%). Recommendations: The study recommended for the importance of managing the various factors associated with stress and providing recreational program to promote their health.